Does The Value of the Company Affected Intellectual Capital with Financial Performance as Interesting Variables? - Rio Ahmad Junaedi; Elva Nuraina; Nur Wahyuning Sulistyowati Nur (Yayasan Ilomata, 2020)
This study aims to examine the effect of intellectual capital on firm value through financial performance as an intervening variable in the property and real estate sub-sector companies which is quantitative research by applying hypothesis testing and conducting path analysis using linear regression. To test the influence of mediation in this study applying the Sobel test with the results of financial performance cannot mediate the relationship of intellectual capital and firm value because financial performance is not the only factor that influences the movement of company values, and intellectual capital itself is a factor that cannot be measured directly different from financial performance.